Morphotectonic forcing and anthropogenic impact behind a recently emerged relict island of the Brahmaputra River. Issue 13 (26th July 2022) - Gogoi, Priti Rekha; Chetia, Monisha; Borgohain, Supriya; Bora, Malobika; Kumar, Adesh; Lahiri, Siddhartha Kumar
Abstract: Large rivers can be significantly impacted upon by both tectonics and human activities; yet, there are very few studies where these natural and anthropogenic impacts combine. A new river island called Dibru‐Saikhoa has appeared very recently on the Brahmaputra valley map in Assam. More than 200 km 2 in area, it is situated in the extreme upstream reach of the Brahmaputra River and represents the second biggest relict island after Majuli (with a present area of ~500 km 2 ). The cause of the formation of this island is generally attributed to river dynamics, with only a minor anthropogenic role. However, our study, considering morphological changes from 1915 to 2019 and subsurface geophysical data, suggests that the anthropogenic factor was an important 'trigger' of island formation, acting on a system made sensitive to change by the combination of local tectonics and rapidly changing sediment influx. Making use of the satellite‐borne Bouguer gravity data and ground survey‐based seismic sections, we located some of the prominent blind faults. Taking into consideration recent activation and interplay of these faults, the mode of accommodation space generation, and aggradation characteristics due to fluvial processes, we suggest a multi‐order mechanism of formation of this relict island. The first‐order trigger is due to the unstable river morphology of the Siang, which is responding to tilting of the valley floor as a co‐seismic phenomenon, and subsequently influences two other rivers—the Dibang and the Lohit. Second‐order forcing comes from intra‐plate residual pop‐up that comes into play due to uneven sediment loading. The third‐order forcing is inter‐plate suturing, which causes arching and fracturing of the basement. Abstract : In 1995, a new island called Dibru‐Saikhoa having more than 200 km 2 of area started forming at the confluence of three rivers from where the Brahmaputra originates in India. During 1975‐2019, the Siang River, flowing along the western side of the island, experienced major morphological changes likely related to under‐reported dam site breaches in the Chinese part of the Siang River during the 2000s. Satellite‐borne gravity and seismic land data helped establish subsurface control behind the island's stability.